Desenvolvimento de método de decomposição por via úmida assistida por radiação micro-ondas em cavidade de digestão pressurizada e determinação de metais e não-metais por técnicas com plasma para plantas medicinais - Gonçalves, Ariadne Gabriela Loreto Peres (2025)
In the present work, a sample preparation method was developed based on wet decomposition assisted by microwave radiation in a pressurized digestion cavity (MAWD-PDC), employing high sample masses and diluted acids. The applicability of the method was demonstrated for medicinal plants, followed by the determination of As, Ba, Ca, Cd, Co, Cr, Cu, Fe, Hg, K, Li, Mg, Mn, Mo, Na, Ni, P, Pb, S, Se, Sn, Sr, and V by inductively coupled plasma optical emission spectrometry (ICP-OES) and inductively coupled plasma mass spectrometry (ICP-MS). For the development of the proposed method, the following parameters were evaluated: (i) irradiation program (temperature: 230 to 280 ºC and time: 20 to 50 min); (ii) sample mass: 0.5 to 2.5 g; (iii) concentration (7 and 8 mol L-1 ) and volume (6 to 15 mL) of HNO3. Solutions with a low carbon content of 1.00 ± 0.01% (357 ± 1 mg L-1 of C) and residual acidity of 21.6% were obtained using 2.0 g of sample and 15 mL of 8 mol L-1 HNO₃ under the following irradiation program: (i) 10 min ramp (200 ºC); (ii) 10 min hold (200 ºC); (iii) 10 min ramp (250 ºC); (iv) 20 min hold (250 ºC); (v) cooling to 70 ºC. Method validation was carried out by evaluating the parameters of selectivity, linearity, robustness, precision (intermediate and repeatability), accuracy, limits of detection (LODs), and limits of quantification (LOQs). Accuracy was assessed using the CRM CTA-OTL-1 Oriental Tobacco Leaves, where agreements of 94 to 104% with RSDs below 5% were obtained for all analytes determined. In addition, the results obtained with the proposed method were compared with two microwave-assisted decomposition methods: (i) using quartz vessels (HNO3 only) and (ii) using PTFE-TFM vessels (HF and HNO3). Finally, the proposed method was applied to the decomposition of eight plant samples, yielding agreements of 90 to 109%, with RSDs lower than 8%. The use of MAWD-PDC combined with ICP-OES and ICP-MS determinations presented advantages by enabling the use of high sample masses and diluted acidic solutions, resulting in low limits of quantification and thus allowing the determination of analytes at trace levels.